If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(m-3)+3m-7m=43
We move all terms to the left:
9(m-3)+3m-7m-(43)=0
We add all the numbers together, and all the variables
-4m+9(m-3)-43=0
We multiply parentheses
-4m+9m-27-43=0
We add all the numbers together, and all the variables
5m-70=0
We move all terms containing m to the left, all other terms to the right
5m=70
m=70/5
m=14
| 16-32b+12=-196 | | d-8/−2=12 | | 16.78+10.18-3.1v=-17.69-7.8v | | 9x-7=-19 | | -19-8u=15-14u+20 | | 15=10d–15 | | -2/5=4x-1/7 | | 17.1p-17.9p+9.57=1.07-17.8p | | 2(3x+4)=6x-7 | | 3c-20+6c=10+6c | | (x-25)(x+24)=0 | | (x-25)(x+24)=6000 | | 7/2x=5/6 | | 18f-20f+18=-4f-10 | | (x-25)(x+24)=600 | | (x-25)(x+13)=325 | | 1=-1+t6 | | 19x=-12x | | 25=-2r+3 | | -9.1d+10.8=6.02-2.2d+19.96 | | 9=3(q+8) | | -h-18=18+4+4h | | -6q-1+7q=2q+14 | | 4=2/3(r-6) | | 3x+7x=-70 | | 8+14b-b=12b-8 | | 7(b+3)+5(b+9)=1 | | 7q+16=44 | | -5x+x/7=-3 | | -17=n-7/3 | | -7(y+4)=-5y-3 | | 5(4z+5)=8z+1 |